HISTORIOGRAFI PERKEMBANGAN HADIS DI NUSANTARA ABAD XX: Kitab Al-Arba’ūna Ḥadīṡan Karya Syeikh Muhammad Yasin Al-Fadani - Saniatul Hidayah (DIRAYAH : Jurnal Ilmu Hadis, 2023)
Sheikh Muhammad Yasin Al-Fadani is one of the hadith experts to be nicknamed Musnid al-Dunya and has an important role in the development of ulum al-hadis in the 20th century. He is one of the Indonesian scholars whose reputation and some of his works in the field of hadith are internationally recognized and clarify the history of the development of hadith in Indonesia. One of his works that will be discussed in this study is the book Al-Arba'ūna Ḥadīthan. The purpose of this study is none other than to obtain an overview of the characteristics of the book of Arba'una Hadithan min Arba'ina Kitaban an Arba'ina Syaikhan. In addition, to find out the position of Shaykh Muhammad Yasin al-Fadani in the science of hadith and its influence in the archipelago. The research method presented in this study is descriptive-analytical which plays a role by providing an overview of the issues raised and providing an analysis of the problem so that it is able to provide answers to these problems. The results of this study found that the role that Sheikh Muhammad Yasin Al-Fadani contributed to the development of hadith was that he wrote several books in various scientific disciplines, including the field of hadith.  The motivation for the preparation of the book of al-Arba'una Hadithan by Shaykh Muhammad Yasin al-Fadani was to emphasize his reputation among the great scholars of the twentieth century, as a scholar who has a fairly extensive knowledge of hadith, because mastering forty books of hadith collections is not an easy matter and the preparation of this book has begun to be rare.